Investigating polymorphisms related to chronic kidney disease and the effect of health and nursing education on self-management ability and quality of life in hemodialysis patients: Quality of Life of Hemodialysis Patients - Qu, Xiaoxiao; Shen, Peng (Cellular and Molecular Biology, 2023)
The effects of health and nursing education are fundamental and essential in achieving the desired quality of life. In recent years, the impact of health and nursing education and self-management ability in many diseases, including kidney patients and those undergoing dialysis and hemodialysis, have been highly regarded. Studies have shown that modern nursing training and self-management ability have an influential role in the treatment process of hemodialysis patients. In general, self-management is a common term in health education and includes symptom management, treatment principles, consequences, and lifestyle changes to maintain and improve quality of life. Planning and continuity of care are necessary for self-management, and the set of these factors is an important and effective issue in kidney and hemodialysis patients and has caused hope, encouragement, and encouragement to more and more patients, improving their quality of life and correct use of healthcare services. In this study, we investigated some health management parameters in the quality of life of hemodialysis patients. The results of this study showed that family support, self-management of personnel, and the nursing system have a positive and significant correlation with the quality of life in these patients (p=0.002). This means that family and social support along with the modern nursing system and self-management can lead to an increase in the quality of life in hemodialysis patients. Also, the results of polymorphism analysis in the GATM locus related to chronic kidney disease showed that the frequency of the A allele in SNP rs2453533-GATM is higher in CKD patients independent of dialysis (non-dialysis) compared to healthy people. Also, the intronic C allele of SNP rs4293393 (UMOD) was more common in healthy subjects than in CKD patients, and the intronic T allele of SNP rs9895661 (BCAS3) is associated with a decrease in eGFRcys and eGFRcrea.